2014
DOI: 10.1007/s00438-014-0909-2
|View full text |Cite
|
Sign up to set email alerts
|

Full-genome identification and characterization of NBS-encoding disease resistance genes in wheat

Abstract: Host resistance is the most economical, effective and ecologically sustainable method of controlling diseases in crop plants. In bread wheat, despite the high number of resistance loci that have been cataloged to date, only few have been cloned, underlying the need for genomics-guided investigations capable of providing a prompt and acute knowledge on the identity of effective resistance genes that can be used in breeding programs. Proteins with a nucleotide-binding site (NBS) encoded by the major plant diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…For H. vulgare and T. aestivum, 318 and 580 NBS-type gene models previously predicted from the whole genome shotgun sequence assembly of barley cv. Bowman and the LCG assembly of T. aestivum, respectively [15] were used in this study. From both sets, we have selected 257 barley and 286 wheat NBS gene models, following examination of the conservation of core NBS with MEME.…”
Section: Data Mining Of Nbs Genes In Poaceaementioning
confidence: 99%
See 1 more Smart Citation
“…For H. vulgare and T. aestivum, 318 and 580 NBS-type gene models previously predicted from the whole genome shotgun sequence assembly of barley cv. Bowman and the LCG assembly of T. aestivum, respectively [15] were used in this study. From both sets, we have selected 257 barley and 286 wheat NBS gene models, following examination of the conservation of core NBS with MEME.…”
Section: Data Mining Of Nbs Genes In Poaceaementioning
confidence: 99%
“…Studies of the NBS gene family have been performed in many monocot and dicot plant species, such as Arabidopsis [7], rice [8], Medicago truncatula [9], Poplar [10], grape [11], sorghum [12], Lotus japonica [13], Brassica rapa [14], Triticum aestivum [15], Brachypodium distachyon [16] and Hordeum vulgare (Y. Habachi-Houimli, Y. Khalfallah, H. Makni, M. Makni, D. Bouktila, unpublished data). All results have shown that the size of this gene family differs in each species.…”
Section: Introductionmentioning
confidence: 99%
“…Negotiating this terrain is no simple task. Wheat is no exception and contains ∼600 NB-LRRs ( Bouktila et al, 2014 ; IWGSC, 2014 ), although this is most likely an underestimate because short read sequencing technologies lack the discriminatory power to assemble such large gene families. An accurate, high-throughput, and cost-efficient long-read technology is required to overcome this limitation.…”
Section: Future Perspectivementioning
confidence: 99%
“…The evolution of NLR and RLK gene sequences in plant genomes is very dynamic. Comparative genomic analyses have indicated that plant genomes encode hundreds of NLR and RLK genes (Meyers et al ., ; Afzal et al ., ; Bouktila et al ., ). Apparently, both whole genome and segmental duplications have contributed to the large family number of these R genes (Meyers et al ., ).…”
Section: Introductionmentioning
confidence: 97%